The Principal's Democratic Leadership Style In Improving Teacher Discipliner At SMP Negeri 9 Samarinda - Diana Rofiqoh; Made Ngurah Partha; Indah Permatasari (Faculty of Teacher Training and Education, Mulawarman University, 2022)
This study aims to determine the democratic leadership style of the principal in improving teacher discipline at SMP Negeri 9 Samarinda. This research is a qualitative descriptive study. Informants in this study were principals, vice principals, teachers and administrative staff of SMP Negeri 9 Samarinda. The results of this study indicate that the democratic leadership style of the principal of SMP Negeri 9 Samarinda has been going well, it can be seen that the principal has reflected a leadership style that always involves teachers in decision making and is carried out by means of deliberation. The principal appreciates the potential of each teacher by giving awards in the form of praise, congratulations, meals and holidays together. The principal also listens and provides opportunities for teachers to convey any criticism, suggestions or opinions. The principal has done good cooperation by going directly to the field with the teacher. The democratic leadership style applied by the principal of SMP Negeri 9 Samarinda can affect teacher discipline, with this leadership style making the teacher always present on time, implementing it in accordance with applicable regulations, polite behavior at school and responsible for carrying out tasks. This is indirectly proven that the discipline achieved by the teacher is influenced by the leadership style that is directly applied by the principal of SMP Negeri 9 Samarinda.